Development of a Meeting Room Reservation System in the Food and Beverage Industry - Achmad Aly Abdulloh; Mamluatul Hani’ah; Vivi Nur Wijayaningrum (Journal of INISTA, 2026)
The manual process of meeting room reservations often takes considerable time and creates inefficiency, especially when coordinating schedules among multiple users. In addition, searching for meeting-related information is not yet integrated, and the absence of automatic reminders often causes users to miss scheduled meetings. To address these issues, a web-based system was developed to manage meeting room reservations digitally. The system includes an information search feature using a chatbot and automatic reminders integrated with Google Calendar or Outlook. The prototype method was applied in the development process. To ensure the system meets user needs, evaluations were carried out through functional testing, the User Experience Questionnaire (UEQ), and time efficiency testing. The functional testing results show that the system works properly and meets user requirements. Meanwhile, UEQ results indicate that all aspects Attractiveness, Perspicuity, Efficiency, Dependability, and Stimulation achieved the “Excellent” category. The highest score was for Stimulation at 2.531, suggesting the system provides an enjoyable, non-monotonous experience that fosters user engagement. In terms of efficiency, manual reservations required between 1,245 and 1,560 seconds, depending on the responsiveness of the admin or receptionist. After system implementation, booking time was reduced to 35 – 50 seconds. This shows an improvement in reservation efficiency of about 96%.